2010
DOI: 10.1089/aid.2009.0241
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of Impact of Maternal HIV Infection on Immunoglobulin Levels in HIV-Exposed Uninfected Children

Abstract: HIV infection affects B cell function and is associated with increased immunoglobulin levels, including in HIV-infected pregnant women. It is unknown if maternal HIV infection affects immunoglobulins in their uninfected children. We investigated this using prospective longitudinal data from children born to HIV-infected women enrolled in the European Collaborative Study (ECS). Data from children enrolled in the European Paediatric Hepatitis C Virus Network (EPHN) were used as a comparison group. Associations b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
27
0

Year Published

2012
2012
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 40 publications
1
27
0
Order By: Relevance
“…Some studies have shown a more robust antibody response to vaccines among HEU infants as compared to unexposed, uninfected controls [44,45]. When compared to Hepatitis C exposed infants, HEU infants have been shown to have lower levels of transferred maternal antibodies at birth and significantly higher total immunoglobulin levels until 2 years of age [46], and it is thought that reduced maternal antibody interference with vaccines may contribute to a stronger vaccine response. However, others studies have reported decreased neutralizing-antibody titres to the oral poliovirus vaccine [47] and diminished response to the Hepatitis B vaccine among HEU infants [48].…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown a more robust antibody response to vaccines among HEU infants as compared to unexposed, uninfected controls [44,45]. When compared to Hepatitis C exposed infants, HEU infants have been shown to have lower levels of transferred maternal antibodies at birth and significantly higher total immunoglobulin levels until 2 years of age [46], and it is thought that reduced maternal antibody interference with vaccines may contribute to a stronger vaccine response. However, others studies have reported decreased neutralizing-antibody titres to the oral poliovirus vaccine [47] and diminished response to the Hepatitis B vaccine among HEU infants [48].…”
Section: Discussionmentioning
confidence: 99%
“…Evidence suggests presence of abnormalities of fetal immune maturation associated with in-utero exposure to HIV which may persist into childhood in a subtle form even in the absence of perinatal HIV transmission, including lower naïve CD4 + cell counts and thymic output in PHEU infants [25]; presence of HIV-specific CD4 + and CD8 + T cells in PHEU children as old as 7 years [26]; increased IgG, IgM, and IgA levels at 24 months of age [27]; and altered cell-mediated or antibody responses to certain vaccines (Bacillus Calmette-Guérin, pertussis, pneumococcus, and tetanus toxoid) [28]. In-utero exposure to maternal infections and immune activation during critical times of development has been associated with increased risk of autism [29], schizophrenia [30], and bipolar disorder [31].…”
Section: Discussionmentioning
confidence: 99%
“…Mortality in this population is higher than in infants of uninfected mothers, and these children are at increased risk of pneumonia and diarrhea, which may relate in part to altered immune maturation and function in HEU infants compared with those in unexposed infants of HIV-uninfected mothers (7)(8)(9)(10)(11). Such potential immune impairment may also compromise responses to primary vaccination in the first year of life and lead to specific susceptibility to vaccine-preventable illnesses, including Hib (12).…”
mentioning
confidence: 99%